Frit for massive rock glaze and preparation method thereof

By using waste glaze, waste roll rod slag and waste edge slag, the problem of non-renewable resources and difficult waste to utilize in the pottery industry is solved, and efficient reuse and excellent performance fuse preparation is achieved.

CN119528436APending Publication Date: 2025-02-28HUBEI HANGRUI CERAMIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840632.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing natural mineral frit resources used in the ceramic construction industry are not renewable, resulting in the gradual depletion of resources and the waste generated in ceramic production is difficult to effectively utilize, which has the problem of sustainable development.

Method used

Waste glaze, waste roll rod slag, waste edge slag and other wastes are used as the main raw materials, combined with additives such as bentonite, borax, wollastonite and zinc oxide, and fuses for rock glaze are prepared through specific process steps.

Benefits of technology

The efficient reuse of waste is achieved, and the production cost is reduced. At the same time, the frit produced has high hardness, good wear resistance and excellent permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187887230000041
    Figure BDA0005187887230000041
  • Figure BDA0005187887230000051
    Figure BDA0005187887230000051
Patent Text Reader

Abstract

The invention provides a frit for massive rock glaze and a preparation method of the frit. The frit comprises the following raw material components in percentage by mass: 30-50% of waste glaze, 20-30% of waste roller slag, 20-30% of waste edging slag, 5-10% of boric acid, 0-10% of bentonite, 0-8% of borax, 0-10% of wollastonite and 0-4% of zinc oxide. The frit for the massive rock glaze is prepared from the waste roller rod slag, the waste edging slag and the waste glaze which are generated in pottery enterprise production and matched with the bentonite, the borax, the wollastonite and other raw materials, so that waste is recycled, the production cost is reduced, and the prepared frit has multiple properties of high hardness, good abrasion resistance and good transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a frit for rock glaze and a preparation method thereof. Background Art

[0002] At present, most of the frits used in the ceramic industry are made of natural minerals, which are processed through crushing, grinding, iron removal, batching, melting, water quenching, and post-processing. However, since natural minerals are non-renewable resources, with continuous development, the available non-renewable resources will become less and less. At the same time, certain wastes are also generated in the production of ceramics. Based on this situation, how to seek a sustainable development path is a sword hanging over the ceramic industry. Summary of the invention

[0003] The object of the present invention is to provide a frit for rock glaze, which can at least solve some of the defects in the prior art.

[0004] To achieve the above object, the present invention adopts the following technical solution:

[0005] A frit for rock glaze comprises the following raw material components by mass percentage: 30-50% of waste glaze, 20-30% of waste roller residue, 20-30% of waste grinding residue, 5-10% of boric acid, 0-10% of bentonite, 0-8% of borax, 0-10% of wollastonite and 0-4% of zinc oxide.

[0006] Furthermore, in the waste glaze, the silicon content is greater than 45%, the aluminum content is greater than 12%, and the calcium content is greater than 5%.

[0007] Furthermore, in the waste roller slag, the silicon content is greater than 65%, the aluminum content is greater than 15%, the potassium content is greater than 3%, and the sodium content is greater than 2%.

[0008] Furthermore, in the waste grinding slag, the aluminum content is greater than 70%, and the zirconium content is greater than 5%.

[0009] Furthermore, the added amount of the bentonite accounts for 3-5% of the total mass of the raw materials.

[0010] Furthermore, the added amount of borax accounts for 2-4% of the total mass of the raw materials.

[0011] Furthermore, the added amount of wollastonite accounts for 5-7% of the total mass of the raw materials.

[0012] Furthermore, the added amount of zinc oxide accounts for 1-4% by mass of the total mass of the raw materials.

[0013] In addition, the present invention also provides a method for preparing the above-mentioned frit for rock glaze, comprising the following steps:

[0014] S1, raw material pretreatment, crushing and grinding the waste glaze, waste roller slag and waste grinding slag to control the particle size to below 325 mesh;

[0015] S2, performing physical sintering and chemical composition inspection on the waste glaze, waste roller residue and waste grinding residue pretreated in step S1, and determining the amount of each raw material component according to the inspection results;

[0016] S3, weighing each raw material according to the raw material component amount determined in step S2 and mixing them evenly;

[0017] S4, melting the raw material mixture at 1400-1600° C. and keeping the mixture in a molten state for 30-60 minutes;

[0018] S5. Drop the melt into cold water for quenching, and then dry the quenched melt.

[0019] Furthermore, after the raw materials are mixed in step S3, the raw material mixture is screened to remove iron.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The frit for rock glaze provided by the present invention is made of waste roller slag, waste grinding slag, waste glaze generated in the production of ceramic enterprises, in combination with raw materials such as bentonite, borax and wollastonite. It not only realizes the reuse of waste and reduces production costs, but also the prepared frit has the multiple properties of high hardness, good abrasion resistance and good transparency. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Traditional frit dry particles are made from natural combustion minerals, which not only have high production costs and are not conducive to sustainable development, but also have a homogeneous amorphous internal structure without any crystal phase formation, resulting in reduced hardness and wear resistance of the frit. When using these traditional frit dry particles to make glazes, in order to improve their wear resistance, high-temperature raw materials such as quartz are generally added to the glaze, but this also leads to poor transparency of the glaze.

[0024] Based on this, the present invention provides a frit for rock glaze, comprising the following raw material components in percentage by mass: 30-50% of waste glaze, 20-30% of waste roller slag, 20-30% of waste grinding slag, 5-10% of boric acid, 0-10% of bentonite, 0-8% of borax, 0-10% of wollastonite, and 0-4% of zinc oxide.

[0025] Among them, the silicon content of the waste glaze is greater than 45%, the aluminum content is greater than 12%, and the calcium content is greater than 5%; the silicon content of the waste roller slag is greater than 65%, the aluminum content is greater than 15%, the potassium content is greater than 3%, and the sodium content is greater than 2%; the aluminum content of the waste grinding slag is greater than 70%, and the zirconium content is greater than 5%.

[0026] In the present invention, waste glaze is used as a flux for the frit, and the waste glaze can be recycled to improve its economic value; waste roller slag contains alumina and zirconium oxide, which can be used as a raw material for the frit to improve the hardness of the frit; waste grinding slag is used as a flux in the frit to provide potassium and sodium elements for the frit to reduce the firing temperature, expand the firing range, and improve the gloss and transparency; the role of boric acid is to reduce the temperature and adjust the expansion coefficient of the glaze. The present invention uses waste glaze, waste roller slag, waste grinding slag, and boric acid as raw materials to prepare the frit, and in the melting process, crystals with regular local arrangement are formed, but the whole is still an amorphous state with disorder inside, so that the prepared frit has multiple properties of high hardness, good abrasion resistance, and good transparency.

[0027] Optimally, the amount of bentonite added is 3-5% by weight of the total weight of the raw materials. The addition of bentonite can make the frit suspended when forming the glaze slurry, making the frit slurry composition uniform.

[0028] Preferably, the added amount of borax accounts for 2-4% by mass of the total mass of the raw materials. The addition of borax can further reduce the temperature and adjust the expansion coefficient of the glaze.

[0029] Preferably, the added amount of wollastonite accounts for 5-7% by mass of the total mass of the raw materials. The addition of wollastonite can reduce the expansion coefficient of the formed frit and increase the hardness of the glaze formed by the frit.

[0030] Furthermore, the amount of zinc oxide added is 1-4% by weight of the total weight of the raw materials. The addition of zinc oxide can reduce the sintering temperature of the frit, and the transparency of the glaze formed by the frit can be adjusted by adjusting the amount of zinc oxide added.

[0031] The method for preparing the above-mentioned frit for rock glaze comprises the following steps:

[0032] S1. Raw material pretreatment: crushing and grinding the waste glaze, waste roller slag and waste grinding slag to control the particle size to below 325 mesh.

[0033] S2. Physically sintering and chemical composition testing are performed on the waste glaze, waste roller slag and waste grinding slag pretreated in step S1, and the dosage of each raw material component is determined according to the test results; the designed raw material composition needs to meet the requirement that it can be melted in a crucible at 1400-1600° C. and can be fired into a liquid state or softened to more than 80%.

[0034] S3. Weigh each raw material according to the raw material component dosage determined in step S2 and mix them evenly.

[0035] S4. Melt the raw material mixture at 1400-1600° C. and keep it in a molten state for 30-60 minutes.

[0036] S5. Drop the melt into cold water for quenching, and then dry the quenched melt.

[0037] The properties of the frit for rock glaze of the present invention will be described below by means of specific examples.

[0038] Embodiment 1:

[0039] This embodiment provides a frit for rock glaze, comprising the following raw material components by mass percentage: 50% of waste glaze, 25% of waste roller slag, 20% of waste grinding slag, and 5% of boric acid. The waste glaze, waste roller slag and waste grinding slag are crushed and ground to less than 325 mesh, and the designed amount of raw material mixture is melted at 1400-1600°C, and kept warm for 30-60 minutes in the molten state; then the melt is dripped into cold water for water quenching, and the water-quenched frit is dried.

[0040] Among them, the percentage contents of the main chemical components in waste glaze, waste roller slag and waste grinding slag are shown in Table 1.

[0041] Table 1:

[0042]

[0043]

[0044] The frit prepared in this embodiment is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C. After firing, the hardness and wear resistance of the glaze surface are tested. According to the test, the hardness of the glaze surface made by the frit is 4, the wear resistance is 5, and the glossiness is 40.

[0045] Embodiment 2:

[0046] This embodiment provides a frit for rock glaze, comprising the following raw material components by mass percentage: 30% of waste glaze, 20% of waste roller slag, 20% of waste milling slag, 5% of bentonite, 4% of borax, 7% of wollastonite, 10% of boric acid, and 4% of zinc oxide. The waste glaze, waste roller slag, and waste milling slag are crushed and ground to less than 325 mesh, and the designed amount of raw material mixture is melted at 1400-1600°C and kept warm for 30-60 minutes in the molten state; then the melt is dripped into cold water for water quenching, and the frit after water quenching is dried. Among them, the main chemical components of the waste glaze, waste roller slag, and waste milling slag are the same as those in Example 1.

[0047] The frit prepared in this embodiment is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C. After firing, the hardness and wear resistance of the glaze surface are tested. According to the test, the hardness of the glaze surface made by the frit is 5, the wear resistance is 5, and the glossiness is 35.

[0048] Embodiment 3:

[0049] This embodiment provides a frit for rock glaze, comprising the following raw material components by mass percentage: 30% of waste glaze, 30% of waste roller slag, 20% of waste milling slag, 3% of bentonite, 2% of borax, 5% of wollastonite, 6% of boric acid, and 4% of zinc oxide. The waste glaze, waste roller slag, and waste milling slag are crushed and ground to less than 325 mesh, and the designed amount of raw material mixture is melted at 1400-1600°C and kept warm for 30-60 minutes in the molten state; then the melt is dripped into cold water for water quenching, and the frit after water quenching is dried. Among them, the main chemical components of the waste glaze, waste roller slag, and waste milling slag are the same as those in Example 1.

[0050] The frit prepared in this embodiment is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C. After firing, the hardness and wear resistance of the glaze surface are tested. According to the test, the hardness of the glaze surface made by the frit is 7, the wear resistance is 5, and the glossiness is 30.

[0051] Embodiment 4:

[0052] This embodiment provides a frit for rock glaze, comprising the following raw material components by mass percentage: 30% of waste glaze, 20% of waste roller slag, 30% of waste milling slag, 5% of bentonite, 3% of borax, 5% of wollastonite, 5% of boric acid, and 2% of zinc oxide. The waste glaze, waste roller slag, and waste milling slag are crushed and ground to less than 325 mesh, and the designed amount of raw material mixture is melted at 1400-1600°C and kept warm for 30-60 minutes in the molten state; then the melt is dripped into cold water for water quenching, and the frit after water quenching is dried. Among them, the main chemical components of the waste glaze, waste roller slag, and waste milling slag are the same as those in Example 1.

[0053] The frit prepared in this embodiment is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C. After firing, the hardness and wear resistance of the glaze surface are tested. According to the test, the hardness of the glaze surface made by the frit is 6, the wear resistance is 5, and the glossiness is 40.

[0054] Comparative Example 1:

[0055] This comparative example provides a frit, and its raw material composition is substantially the same as that of the above-mentioned Example 3, except that this comparative example does not contain waste grinding slag, and the proportions of the remaining components are consistent with those of Example 3.

[0056] The frit prepared in this comparative example is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C, and the hardness and wear resistance of the glaze surface are tested after firing. According to the test, the hardness of the glaze surface made by the frit is 7, the wear resistance is 5, and the glossiness is 25.

[0057] Comparative Example 2:

[0058] This comparative example provides a frit, and its raw material composition is substantially the same as that of the above-mentioned Example 3, except that this comparative example does not contain boric acid, and the proportions of the other components are consistent with those of Example 3.

[0059] The frit prepared in this comparative example is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C, and the hardness and wear resistance of the glaze surface are tested after firing. According to the test, the hardness of the glaze surface made by the frit is 5, the wear resistance is 5, and the glossiness is 35.

[0060] Comparative Example 3:

[0061] This comparative example provides a frit, and its raw material composition is substantially the same as that of the above-mentioned Example 3, except that this comparative example does not contain waste roller slag, and the proportions of the other components are consistent with those of Example 3.

[0062] The frit prepared in this comparative example is made into glaze slurry, and then the glaze slurry is scraped onto the green body with a glaze scraper, and then the green body with glaze is placed in an oven for drying, and the glaze surface is fired at 1100-1200°C, and the hardness and wear resistance of the glaze surface are tested after firing. According to the test, the hardness of the glaze surface made by the frit is 4, the wear resistance is 4, and the glossiness is 35.

[0063] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.

Claims

1. A frit for rock glaze, characterized in that: The invention comprises the following raw material components in percentage by mass: 30-50% of waste glaze, 20-30% of waste roller residue, 20-30% of waste grinding residue, 5-10% of boric acid, 0-10% of bentonite, 0-8% of borax, 0-10% of wollastonite and 0-4% of zinc oxide.

2. The frit for rock glaze according to claim 1, characterized in that: The waste glaze has a silicon content greater than 45%, an aluminum content greater than 12%, and a calcium content greater than 5%.

3. The frit for rock glaze according to claim 1, characterized in that: The waste roller slag has a silicon content greater than 65%, an aluminum content greater than 15%, a potassium content greater than 3%, and a sodium content greater than 2%.

4. The frit for rock glaze according to claim 1, characterized in that: The waste grinding slag has an aluminum content greater than 70% and a zirconium content greater than 5%.

5. The frit for rock glaze according to claim 1, characterized in that: The added amount of the bentonite accounts for 3-5% of the total mass of the raw materials.

6. The frit for rock glaze according to claim 1, characterized in that: The added amount of borax accounts for 2-4% of the total mass of the raw materials.

7. The frit for rock glaze according to claim 1, characterized in that: The added amount of wollastonite accounts for 5-7% of the total mass of the raw materials.

8. The frit for rock glaze according to claim 1, characterized in that: The added amount of zinc oxide accounts for 1-4% of the total mass of the raw materials.

9. The method for preparing the frit for rock glaze according to any one of claims 1 to 8, characterized in that: The steps include: S1, raw material pretreatment, crushing and grinding the waste glaze, waste roller slag and waste grinding slag to control the particle size to below 325 mesh; S2, performing physical sintering and chemical composition inspection on the waste glaze, waste roller residue and waste grinding residue pretreated in step S1, and determining the amount of each raw material component according to the inspection results; S3, weighing each raw material according to the raw material component amount determined in step S2 and mixing them evenly; S4, melting the raw material mixture at 1400-1600° C. and keeping the mixture in a molten state for 30-60 minutes; S5. Drop the melt into cold water for quenching, and then dry the quenched melt.

10. The method for preparing the frit for rock glaze according to claim 9, characterized in that: After the raw materials are mixed in step S3, the raw material mixture is screened to remove iron.